Effect of Vitamin E on Serum Urea Level on Gentamicin Induced Nephrotoxicity in Long Evans Rats (Delta Medical College Journal, 2019)
Background: The kidneys have an important role in eliminating the final products of metabolic activities, excreting the drugs and chemicals. A variety of frequently used drugs have been demonstrated to produce nephrotoxic effects.Objective: This study was carried out to observe the effect of vitamin E on gentamicin-induced nephrotoxicity by assessing serum urea level in Long Evans rats.Materials and method: The experimental study was carried out on 40 healthy Long Evans rats of both sex with the weight ranges from 172-255 gm and the age ranges from 7 to 10 weeks. The rats were divided into four groups - Group A (normal control) received normal saline, group B, C and D received gentamicin for 6 days, rats of group C received vitamin E capsule for total 9 days with gentamicin whereas group D received vitamin E capsule for total 10 days with gentamicin. Serum urea level was measured at the end of the experiment.Results: The (mean±SD) serum urea levels in group A, B, C and D were 4.79±0.32, 12.41±1.22, 7.56±1.11 and 7.15±1.09 mmol/L respectively. The differences between groups were highly significant (p0.01) was not significant. Serum urea level of the normal saline control group (group A) was within the normal limit (4.79 mmol/L). Serum urea level in gentamicin treated rats (group B) was more in comparison to gentamicin and vitamin E treated rats (group C & D) and pretreatment with longer duration group (group D) showed lower serum urea value than shorter one (group C) though the groups showed no significant difference.Conclusion: Vitamin E treatment showed some protective effect against gentamicin-induced nephrotoxicity. The results also indicated that effectiveness of vitamin E depends on duration of pretreatment that means the pretreatment duration must be increased to a suitable period for better protection against gentamicin-induced nephrotoxicity.Delta Med Col J. Jan 2019 7(1): 11-15